2016
DOI: 10.1007/s10803-016-2811-8
|View full text |Cite
|
Sign up to set email alerts
|

The Interface of Syntax with Pragmatics and Prosody in Children with Autism Spectrum Disorders

Abstract: In order to study problems of individuals with Autism Spectrum Disorders (ASD) with morphosyntax, we investigated twenty high-functioning Greek-speaking children (mean age: 6;11) and twenty age- and language-matched typically developing children on environments that allow or forbid object clitics or their corresponding noun phrase. Children with ASD fell behind typically developing children in comprehending and producing simple clitics and producing noun phrases in focus structures. The two groups performed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…The theory predicts that TD children (and thus children with SLI) will not omit object clitics in Greek, and that was confirmed for TD children by Tsakali and Wexler (2003) and for children with SLI by Manika et al (2011). One such study has already been done in Greek for 6-year-old children with high-functioning autism (Terzi et al, 2016), who show lower clitic production than age and receptive vocabulary matched TD controls, which indicates deviance. In this way, the studies in the field of grammar in autism will advance to the level of the study of the theory of developmental mechanisms, rather than individual constructions, paralleling advances in the study of typical development.…”
Section: Discussionmentioning
confidence: 99%
“…The theory predicts that TD children (and thus children with SLI) will not omit object clitics in Greek, and that was confirmed for TD children by Tsakali and Wexler (2003) and for children with SLI by Manika et al (2011). One such study has already been done in Greek for 6-year-old children with high-functioning autism (Terzi et al, 2016), who show lower clitic production than age and receptive vocabulary matched TD controls, which indicates deviance. In this way, the studies in the field of grammar in autism will advance to the level of the study of the theory of developmental mechanisms, rather than individual constructions, paralleling advances in the study of typical development.…”
Section: Discussionmentioning
confidence: 99%
“…First, patients with aphasia experience significant difficulty understanding and/or producing language, but appear to be largely unimpaired in their ToM reasoning (e.g., Dronkers et al, 1998;Varley & Siegal, 2000;Varley, Siegal & Want, 2001;Apperly et al, 2006;Willems et al, 2011). Conversely, individuals with autism spectrum disorders suffer from ToMor more generalized socialdeficits (e.g., Baron-Cohen et al, 1985;Happé, 1993), yet often have their core linguistic processing abilities intact (e.g., Wilkinson, 1998;Lord & Paul, 1997;Tager-Flusberg, 2006;Asberg, 2010;Terzi, Marinis, & Francis, 2016;Diehl, Bennetto, Young, 2006;Janke, Perovic, 2015;Frith & Happe, 1994). And second, neuroimaging studies with healthy adults have revealed that largely distinct sets of brain regions support ToM vs. language processing abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do so, we did not only assess comprehension and production of simple clitics, but also comprehension and production of clitics in CLLD structures, along with a number of other structures that forbid the use of a clitic pronoun (Terzi et al 2015). The use of clitic pronouns, by contrast to their corresponding DPs, is determined on the basis of specific pragmatic grounds, which are rather well described in the relevant literature -see Mavrogiorgos (2010) for a recent review, and the discussion later in the paper.…”
mentioning
confidence: 99%